A DNA Barcode Dataset for the Aquatic Fauna of the Panama Canal: Novel Resources for Detecting Faunal Change in the Neotropics - Kristin Saltonstall; Rachel Collin; Celestino Aguilar; Fernando Alda; Laura M. Baldrich-Mora; Victor Bravo; María Fernanda Castillo; Sheril Castro; Luis F. De León; Edgardo Díaz-Ferguson; Humberto A. Garcés; Eyda Gómez; et al. (Data)
DNA metabarcoding is a powerful biodiversity monitoring tool, enabling simultaneous assessments of diverse biological communities. However, its accuracy depends on the reliability of reference databases that assign taxonomic identities to obtained sequences. Here we provide a DNA barcode dataset for aquatic fauna of the Panama Canal, a region that connects the Western Atlantic and Eastern Pacific oceans. This unique setting creates opportunities for trans-oceanic dispersal while acting as a modern physical dispersal barrier for some terrestrial organisms. We sequenced 852 specimens from a diverse array of taxa (e.g., fishes, zooplankton, mollusks, arthropods, reptiles, birds, and mammals) using COI, and in some cases, 12S and 16S barcodes. These data were collected for a variety of studies, many of which have sought to understand recent changes in aquatic communities in the Panama Canal. The DNA barcodes presented here are all from captured specimens, which confirms their presence in Panama and, in many cases, inside the Panama Canal. Both native and introduced taxa are included. This dataset represents a valuable resource for environmental DNA (eDNA) work in the Panama Canal region and across the Neotropics aimed at monitoring ecosystem health, tracking non-native and potentially invasive species, and understanding the ecology and distribution of these freshwater and euryhaline taxa.